2019
DOI: 10.21742/ijsbt.2019.7.2.04
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Purchase Intention of Eco-friendly Products: A Cross-Cultural Investigation between Korea and China

Abstract: This study sought to compare the purchase intention of eco-friendly products between Korean and Chinese consumers. For this purpose, it established a conceptual model in which environmental knowledge affects attitude, subjective norm, and perceived behavioral control toward eco-friendly products, which in turn are connected to purchase intention of eco-friendly products. According to the analysis results, in both Korean and Chinese cases consumers' environmental knowledge had a positive effect their attitude t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…According to the previous studies comparing the difference of consumer's behavior according to environmental consciousness, the relationship between environmental consciousness and eco-friendly behavior was high, and consumers with high environmental consciousness were likely to do eco-friendly behavior [7]. Consumers with high sensitivity to environmental pollution, environmental reports, and articles claimed that the consistency of attitude and behavior appeared in the relationship between environmental preservation attitude and eco-friendly behavior [8]. Tognacci et al, [9] also argued that environmental consciousness is an important factor in predicting eco-friendly behavior.…”
Section: Environmental Consciousness and Eco-friendly Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…According to the previous studies comparing the difference of consumer's behavior according to environmental consciousness, the relationship between environmental consciousness and eco-friendly behavior was high, and consumers with high environmental consciousness were likely to do eco-friendly behavior [7]. Consumers with high sensitivity to environmental pollution, environmental reports, and articles claimed that the consistency of attitude and behavior appeared in the relationship between environmental preservation attitude and eco-friendly behavior [8]. Tognacci et al, [9] also argued that environmental consciousness is an important factor in predicting eco-friendly behavior.…”
Section: Environmental Consciousness and Eco-friendly Behaviormentioning
confidence: 99%
“…Through previous studies, China was identified as a country with a strong tendency to collectivism [8]. China, a socialist system, has a very strong tendency to comply with and follow the government's decisions.…”
Section: Cultural Backgroundmentioning
confidence: 99%
“…Therefore, this study was conducted to compare purchase intention of eco-friendly products between Korean and Chinese consumers. The reason for selecting China for the comparison to Korea was that lately China has shown great concerns with environmental issues unlike in the past (Yoon and Joung, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Actually, even though China has been pointed out as one of the countries that have had the strongest effect on the global environment, in the past the Chinese government did not show great interest in and high responsibility for environmental problems (Yoon and Joung, 2019). However, recognizing the seriousness of environmental problems, the government brought the New Environmental Protection Law into effect in 2015, and has led radical changes in environmental attitudes and behavior of individuals and companies at the national level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation